Description of a new Agraecina species from Tunisia (Araneae: Liocranidae), with a review of all species of the genus - Boubakri, Abir; Bosmans, Robert; Pétillon, Julien; Achouri, Mohamed Sghaier (Zootaxa, 2020)
While Liocranidae is a family encompassing 283 species distributed in 32 genera (World Spider Catalog 2019), the genus Agraecina Simon, 1932 currently counts only six described species: Agraecina canariensis Wunderlich, 1992 from the Canaries, A. cristriani (Georgescu, 1989) from Romania, A. hodna Bosmans, 1999 from Algeria, A. lineata (Simon, 1878) from Europe and Kazakhstan, A. rutilia (Simon, 1897) from Sierrra Leone, and A. scupiensis Deltshev, 2016 from Macedonia. During an ecological survey in the north of Tunisia, a new Agraecina species was discovered and is described here. Spiders were collected using pitfall traps in a salt marsh.